ANALISA HASIL INSTALASI PENGELOLAAN AIR LIMBAH RUMAH SAKIT - M Yasir Pohan; Elita Amrina (Jurnal Genta Mulia, 2026)
Hospital is one of the health facilities as an effort to maintain and improve public health. Thepurpose of this study was to evaluate the liquid waste management system at the Hospital.Descriptive research method with a qualitative approach. Data collection was carried out byinterviews, document reviews and direct field observations. The variables studied were theprocess of managing liquid waste originating from the hospital. Research Results Based onthe results of interviews and observations, the management of liquid waste at the Hospital hasan Aerobic method mixed with Enzyme Chemicals. The sources of wastewater that flow intothe Wastewater Treatment Plant come from all activities of the Hospital. showing the resultsof outlet tests with parameters of Temperature, pH, BOD, COD, TSS, oil and fat can be saidto be optimal in the process of processing liquid waste because the results of the Analysishave met the standard quality standards. The conclusion of the characteristics of hospitalliquid waste by testing the outlet has met the standard quality standards.